TRATAMIENTO LAPAROSCÓPICO DEL CÁNCER DE RECTO: RESULTADOS ONCOLÓGICOS A LARGO PLAZO - Rossi, Gustavo; Vaccarezza, Hernán; Vaccaro, Carlos; Mentz, Ricardo; Im, Victor; Benati, Mario; Bonadeo, Fernando; Ojea Quintana, Guillermo (Revista Argentina de Cirugía, 2022)
Background: Even though the laparoscopic approach for rectal cancer has been previously described, its extended application is still controversial and the long-term oncological results are limited. Objective: To analyze the surgical results, local recurrence rate and 5-year survival in patients with rectal cancer operated on by laparoscopy. Secondarily, to compare the survival of patients operated on by laparoscopy with those who required conversion to open surgery. Setting: Private University Hospital Design: Retrospective observational. Material and Methods: One hundred and sixty four consecutive patients undergoing laparoscopic surgery for rectal cancer were analyzed between January 2005 and December 2011. The clinical, pathological and oncological data were collected into a database. Overall and disease free survival at 5 years was estimated by Kaplan-Meier method. Results: 66% of patients had tumors in middle (n=76) and low (n=32) rectum, and 26% (n=43) received neoadjuvant therapy. The sphincter preservation rate was 95%. The median distance between the anastomosis and the anal verge was 5 cm (range: 2 - 12), and a “j” pouch was performed in 8.5%. The overall conversion rate to open surgery was 14.6%. The morbidity and mortality was 19.5% and 0% respectively. The median hospital stay was 3 days (range: 2-28). Surgical margins were negative. The median of lymph nodes harvested was 15 (range: 0-56). According to TNM staging, there were 3.8% for stage 0, 37.8 for stage I, 22.5% for stage II, 29,2% for stage III and 6.7 for stage IV. The median follow up time was 25 months (range: 3-81).